The analysis of problem-based learning implementation and its effect on students creative innovative skills in solving rainbow antimagic coloring based on cognitive style. (May 2020) - Al Jabbar, Z L; Dafik; Hadi, A F; Wangguway, Y; Sulistiyono, B
Abstract: This study aims to determine the application of problem based learning and its effect on students' creative innovative skills in solving rainbow antimagic coloring based on cognitive style. This study used mixed method which combination of qualitative and quantitative research method. This study used research subjects of 41 students in the experiment class and 32 students in the control class who were students in 3 rd semester. Qualitative method is applied to analysis students' creative innovative skills which used data from test result and phase portraits results while quantitative method is used to statistical analysis. There were differences between control and experiment class when it was given a treatment. In control class used conventional learning while in experiment class, we used problem based learning. The statistical result indicates that the sig (2-tailed) significance of the independent sample t-test in post-test was 0.000 or α ≤ 0.05. it can be concluded that there is an effect of used problem based learning in creative innovative skills on solving rainbow antimagic coloring.